Characterization of a bimodal multi-fibre optic clinical probe for in situ tissue diagnosis based on spectrally-and temporally-resolved autofluorescence - Sibai, Mira; Mehidine, Hussein; Devaux, Bertrand; Abi Haidar, Darine (Frontiers in Physics, 2023)
Fibred-based optical spectroscopy is advantageous over imaging due to its sensitivity, practicality and precision, providing point of care diagnosis. The unique advantage is that the sampled volume is well defined by the source-detector geometry and that the functionality of multiple optical techniques can be incorporated into one probe so that more information is gained without extra bulkiness or cost, while also mitigating the limitations of each. This advantage is utilized here to address the limited accuracy in delineating brain tumors, in situ, by simultaneously characterizing tissue based on the spectral and lifetime properties of five endogenous fluorophores commonly present in brain tissue. A multi fibre-optic probe custom-built for neurosurgery with a sterilisable distal end enables this. This paper describes its technical features such as architecture, collection efficiency, sensitivity, spatial resolution and its temporal impulse response. The probe is validated using fluorescent dyes and tissue phantoms. Additionally, the fluorescence spectra from fresh and frozen animal tissue and from an epileptic patient are compared to that obtained from confocal fluorescence microscopy, while the lifetime values are compared to that reported in literature. Finally, the effect of pressure applied to the probe in contact with tissue is discussed.